Assessing the Impacts of Conformational Fluxionality on Copper(II/I) Electron Transfer Self-Exchange - Aditi Singh; Emmanuel Adu Fosu; Shuohao Wang; Elena Jakubikova; Lisa Olshansky (Journal of the American Chemical Society, 2026)
Abstract Typical Cu(II/I) complexes exhibit hallmark structural changes during their electron transfer (ET) reactions that result from the (pseudo) Jahn-Teller distortions and changes in polarizability inherent to their d9/d10 configurations. Given that such structural changes incur large reorganization energy penalties, the slow rates of ET characteristic of these compounds are unsuprising. However, we recently reported a set of Cu(II/I) complexes that undergo significant and well-defined structural changes during their redox reactions yet exhibit rapid (>105 M–1 s–1) ET self-exchange rate constants (k11). To explain these results, we proposed a pre-equilibrium model in which inherent conformational fluxionality in one of the two oxidation states provides access to pathways involving lower reorganization energies during the ET event. Herein, we report our results testing this hypothesis through the preparation and study of a homologous series of compounds exhibiting varying extents of conformational fluxionality in the Cu(I) state. We characterize these compounds electrochemically, structurally, and by variable temperature NMR spectroscopy to provide experimental evidence for increased fluxionality across the series. We then correlate the trend with increasing k11 through NMR linewidth broadening experiments, further taking care to define the impacts of solvent impurities therein. Finally, the nature of the conformational rearrangements and their relation to increased k11 are explored computationally to reveal differential Boltzmann populations of conformers across the series. The cumulative results of these studies support a previously underappreciated strategy for overcoming barriers to slow ET kinetics: namely through the incorporation of conformational fluxionality.